Counting subgroup formula for the groups formed by cartesian Product of the generalized quaternion group with cyclic group of order two (2015)
The main goal of this note is to determine an explicit formula of finite group formed by taking the Cartesian product of the generalized quaternion group of two power order with a order two cyclic group